Effects of short-term rental markets on Lisbon´s housing market : the case of Airbnb - Santos, Catarina de Costa Lourenço e Ávila dos (2019)
This research, aims to assess the impact of home-sharing platforms and short-term rental markets on Lisbon’s housing market. The main question is if Airbnb listings impact house prices. Furthermore, if the impact on house prices differs with the type of Airbnb listings. The high demand for short-term rentals can lead homeowners to switch from supplying the long-term market to suppling the home-sharing market in response to increased demand, thus increasing house prices. Using data for Airbnb listings and data on the price per square meter of sales for the 24 neighborhoods that compose the city of Lisbon, I estimate a fixed effect model at the neighborhood level. The overall results of the investigation suggest that Airbnb presence affects local house prices. Specifically, I find that a 1% increase in Airbnb entire home listings increases house prices by 0,043%, controlling for time fixed effects and differential price trends across neighborhoods. This result is also consistent with the hypothesis that entire home listings may have a bigger impact on house prices than room listings.